Enhancing protection motivation for disaster preparedness among actors at UNESCO-designated heritage sites in Africa - Eze, Emmanuel; Petersen, Maike; Siegmund, Alexander (International journal of disaster risk reduction, 2024)
Heritage sites face escalating threats from natural and human-induced hazards, posing risks to centuries of cultural heritage and environmental diversity. Despite this pressing challenge, there is a notable scarcity of qualitative studies linking protection motivation and disaster preparedness in UNESCO-designated sites. Guided by the Protection Motivation Theory (PMT) this study fills this critical gap by examining these aspects within UNESCO-designated sites in Africa. By adopting a directed qualitative content analysis approach, key informant interviews of 21 actors, covering 10 countries provided pertinent data for this study. While threat appraisal was strong, coping appraisal was weak, with partial disaster preparedness among UNESCO actors. Notably, the absence of fear as a predominant motivating factor for protection and disaster preparedness was compensated by other factors namely: a strong sense of heritage stewardship, and sustainability/resilience commitment. These findings extend the PMT framework and advocate for future research integrating elements of place attachment theory. By leveraging these insights, stakeholders can collaboratively enhance preservation efforts, ensuring the long-term sustainability of Africa's cultural and natural heritage.
Gesehen am 12.12.2024